The importance of endoscopic spinchterotomy in biliary fistulas secondary to hydatid disease of liver - M. Mahir Özmen; Adil TANIK; Arife POLAT; Uğur YILMAZ; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-